End-of-Life Care Patterns at a Community Hospital: The Rest of the Story. (December 2017) - Waite, Kip; Rhule, Jane; Bush, David; Meisenberg, Barry
We undertook a retrospective review of a subset of expired patients at our community hospital to evaluate end-of-life care patterns and the use of advanced care planning tools among patients who died in the hospital. These 162 expired patients fell into 1 of the 3 diagnosis-related groups of cardiac, respiratory, or infectious disease. Seventy-nine percent of patients arrived to the hospital with no requested limitations in the extent of resuscitative efforts, even though 98% of all patients had major or extreme severity of illness and risk of mortality scores. The presence of an advance directive requesting a limitation of resuscitative efforts modestly impacted resources and procedures, even though utilization in this group was high. Among the 21% of patients with preexisting limits, 21% requested more aggressive support during their course. Critical care unit utilization was seen in 69% of patients for a median of 48 hours. A request for palliative care consultation was received in 44% of patients but only occurred in 30% of all patients due to the short period between the consultation request and patient death (median 37 hours). Among this group of dying patients, engagement of the palliative care team came too late in the course of many patients, suggesting that automated tools embedded in the electronic medical record might be helpful in the identification of appropriate patients earlier.